Risk Factors and Intervention Strategies of Heat Stress in Construction Workers: A Systematic Review - Nona Carolina; Oktomi Wijaya (Universitas Airlangga, 2025)
One of the industries that contributes the most to deaths and work accidents during the summer is the construction industry. Health problems due to heat in construction workers in several countries are heat stress. Therefore, this study was conducted by the author with the aim of determining the prevalence and risk factors as well as intervention strategies for heat stress in construction workers. The research conducted by the author used the Systematic Literature Review method with reference to the Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) 2020 guidelines. A total of 2.073 articles were obtained from the Scopus and PubMed databases for analyzed using the Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) 2020 framework by considering the eligibility criteria that have been made. Articles that meet the inclusion criteria are then further analyzed using the Joanna Briggs Institute (JBI) Critical Appraisal checklist to measure the quality of the articles to be reviewed. The high quality of articles is used by researchers as the result of the Systematic Literature Review. The result of the Systematic Literature Review analyzed 13 articles qualitatively using a narrative synthesis approach. From these results, it is known that the prevalence of heat stress in construction workers is 30%. Risk factors for heat stress in construction workers briefly consist of individual, environmental, organizational, psychosocial, economic, workload, and history of chronic disease factors. Meanwhile, the heat stress intervention strategy for construction workers that can be carried out is to regulate and adjust body temperature to the environment (acclimatization), provide facilities for heat stress mitigation, work area engineering, administrative arrangements in the work environment, adjustment of Personal Protective Equipment, and health promotion.